Atiprimod Triggered Apoptotic Cell Death Via Acting on PERK/eIF2 alpha/ATF4/CHOP and STAT3/NF-Kappa B axis in MDA-MB-231 and MDA-MB-468 Breast Cancer Cells - Çoker-Gürkan, Ajda; CAN, ESİN; ŞAHİN, SEMANUR; ARISAN, ELİF DAMLA; YERLİKAYA, PINAR OBAKAN (Springer, 2021)
Purpose The constitutive activation of STAT3 through receptor tyrosine kinases triggered breast cancer cell growth and invasion-metastasis. Atiprimod impacts anti-proliferative, anti-carcinogenic effects in hepatocellular carcinoma, lymphoma, multiple myeloma via hindering the biological activity of STAT3. Dose-dependent atiprimod evokes first autophagy as a survival mechanism and then apoptosis due to prolonged ER stress in pituitary adenoma cells. The therapeutic efficiency and mechanistic action of atiprimod in breast cancer cells have not been investigated yet. Thus, we aimed to modulate the pivotal role of ER stress in atiprimod-triggered apoptosis in MDA-MB-231 and MDA-MB-468 breast cancer cells. Results Dose- and time-dependent atiprimod treatment inhibits cell viability and colony formation in MDA-MB-468 and MDA-MB-231 breast cancer cells. A moderate dose of atiprimod (2 mu M) inhibited STAT3 phosphorylation at Tyr705 residue and also suppressed the total expression level of p65. In addition, nuclear localization of STAT1, 3, and NF-kappa B was prevented by atiprimod exposure in MDA-MB-231 and MDA-MB-468 cells. Atiprimod evokes PERK, BiP, ATF-4, CHOP upregulation, and PERK (Thr980), eIF2 alpha (Ser51) phosphorylation's. However, atiprimod suppressed IRE1 alpha-mediated Atg-3, 5, 7, 12 protein expressions and no alteration was observed on Beclin-1, p62 expression levels. PERK/eIF2 alpha/ATF4/CHOP axis pivotal role in atiprimod-mediated G1/S arrest and apoptosis via Bak, Bax, Bim, and PUMA upregulation in MDA-MB-468 cells. Moreover, atiprimod renders MDA-MB-231 more vulnerable to type I programmed cell death by plasmid-mediated increased STAT3 expression. Conclusion Atiprimod induced prolonged ER stress-mediated apoptosis via both activating PERK/eIF2 alpha/ATF4/CHOP axis and suppressing STAT3/NF-kappa B transcription factors nuclear migration in TBNC cells.
Keywords: Apoptosis; Autophagy; Atiprimod; Cancer; Cell Cycle; Endoplasmic Reticulum